Wireless Technologies for Social Distancing in the Time of COVID-19: Literature Review, Open Issues, and Limitations - Murad S.S.; Yussof S.; Badeel R. (MDPI, 2023)
Coronaviruses; COVID-19; Emerging technologies; Essential elements; Literature reviews; Pandemic; Research analysis; Research review; Social distancing; Wireless technologies; Coronavirus; epidemiology; human; motivation; pandemic; prevention and control; wireless communication; COVID-19; Humans; Motivation; Pandemics; Physical Distancing; Wireless Technology